Determination of norfloxacin and ciprofloxacin concentrations in serum and urine by high-pressure liquid chromatography. - Morton, S J (1986)
A high-pressure liquid chromatographic method for the determination of norfloxacin or ciprofloxacin concentrations in body fluids was developed and compared with a standard bioassay. The high-pressure liquid chromatographic assay utilizes a reverse-phase C18 column, an internal standard, and fluorescence detection, with reproducibility studies yielding coefficients of variation ranging from 0.6 to 3.7% and 0.9 to 2.7% for norfloxacin and ciprofloxacin, respectively. Correlation coefficients with the bioassay were 0.966 for norfloxacin and 0.952 for ciprofloxacin.